2007
DOI: 10.1080/10408390600698197
|View full text |Cite
|
Sign up to set email alerts
|

Saponins: Properties, Applications and Processing

Abstract: Saponins are a diverse group of compounds widely distributed in the plant kingdom, which are characterized by their structure containing a triterpene or steroid aglycone and one or more sugar chains. Consumer demand for natural products coupled with their physicochemical (surfactant) properties and mounting evidence on their biological activity (such as anticancer and anticholesterol activity) has led to the emergence of saponins as commercially significant compounds with expanding applications in food, cosmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
358
0
13

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 824 publications
(375 citation statements)
references
References 138 publications
4
358
0
13
Order By: Relevance
“…All legumes have triterpene-type saponins (Muzquiz et al, 2012). In fact, while triterpenoid saponins are mainly found in Magnoliopsida (former dicotyledons), steroidal saponins are more abundant in Liliopsida (former Gry et al (2006), Hylands and Mansour (1982), Hylands and Salama (1976), Oobayashi et al (1992), Pohlmann (1975 monocotyledons) (Güçlü-Üstündağ and Mazza, 2007;Podolak et al, 2010). The structural complexity of these compounds results in a wide range of biological properties (Güçlü-Üstündağ and Mazza, 2007) among which in vitro haemolytic activity has been one of the most investigated ones.…”
Section: Saponinsmentioning
confidence: 99%
See 1 more Smart Citation
“…All legumes have triterpene-type saponins (Muzquiz et al, 2012). In fact, while triterpenoid saponins are mainly found in Magnoliopsida (former dicotyledons), steroidal saponins are more abundant in Liliopsida (former Gry et al (2006), Hylands and Mansour (1982), Hylands and Salama (1976), Oobayashi et al (1992), Pohlmann (1975 monocotyledons) (Güçlü-Üstündağ and Mazza, 2007;Podolak et al, 2010). The structural complexity of these compounds results in a wide range of biological properties (Güçlü-Üstündağ and Mazza, 2007) among which in vitro haemolytic activity has been one of the most investigated ones.…”
Section: Saponinsmentioning
confidence: 99%
“…Saponins are a diverse group of secondary metabolites characterized by a structure containing a triterpene or steroid aglycone called sapogenin and one or more sugar chains (Güçlü-Üstündağ and Mazza, 2007;Podolak et al, 2010), which have already been identified in more than 100 plant families. The consumption of saponin-containing plant foods may be associated with beneficial and adverse effects.…”
Section: Saponinsmentioning
confidence: 99%
“…Soy lecithin is classified as a natural zwitterionic surfactant, and applications of this surfactant include emulsification and film formation [9] . Saponins are soluble in water and have in its structure a steroidal hydrophobic portion or triterpenoid and one or more carbohydrates chains, being considered as surfactants agents [10] . This feature ensures functionality in reducing surface tension of water, with consequent action as detergent, emulsifying and foaming, so it is widely used in food and other industrial applications [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Saponins are soluble in water and have in its structure a steroidal hydrophobic portion or triterpenoid and one or more carbohydrates chains, being considered as surfactants agents [10] . This feature ensures functionality in reducing surface tension of water, with consequent action as detergent, emulsifying and foaming, so it is widely used in food and other industrial applications [10] . Many sources of saponins have been used commercially, but only two are currently permitted as additives in foods: Quillaya saponaria and Yucca Schidigera extracts.…”
Section: Introductionmentioning
confidence: 99%
“…3B below). Because of their surface active properties, 13,[18][19][20][21][22] soyasaponin Ba would be dissolved or dispersed into the borax solution in the presence of soyasaponin Bb.…”
mentioning
confidence: 99%